Modeling and control for heating, ventilation and air conditioning system - Yeo, Hui Siong (2019)
The Heating, Ventilation and Air Conditioning (HVAC) system is designed to provide comfortable indoor temperature environment to occupants and research has shown that it contributed to almost 50% of total energy consumptions in buildings. Air Handling Unit (AHU) is a major component in HVAC that contributes to the overall ventilation performance and the chilled water supply (CHWS) in AHU affects the capability of supply air temperature response. To maintain the desired AHU temperature set point, we need to understand the AHU system responses from the valve modulation of CHWS unit. The First Order Plus Dead Time (FOPDT) model is a common empirical design used to derive the HVAC system. Due to the complexity of HVAC system, there are several approaches which can be proposed for local control of AHU supply air temperature. The model-based IMC-PI controllers was adopted to improve the set point responses and to effectively control the AHU air supply temperature. The IMC-PI controllers could be easily tuned with the advantage of a single tuning parameter. MATLAB’s Simulink was used in the simulations and evaluations of controllers. The resulted simulations of the IMC-PI controllers had shown fast responses and maintained its desired temperature set points. The evaluated controllers can be digitally implemented for the HVAC system and an AHU graphical user interface is designed to improve the convenience of remote monitoring and controls.